Caracterização física e mecânica do pecíolo de Inajá (Maximiliana Maripa) na microrregião de Santarém - PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The Inajá (Maximiliana maripa) petiole comes from a native palm tree from Brazil, which can be found throughout the Brazilian Amazon and neighboring countries, with its highest incidence in the state of Pará and the Amazon River estuary, reaching Maranhão. The inajazeiro is mostly used by local residents as food, biofuel source and as raw material for the cosmetics and medicine industry. Given the abundance and potential of this natural resource, little has been studied about palm petioles, especially the Inajá petiole. The existing literature on the use of palm in the area of technological exploration is insufficient, and there is little bibliographic reference indicating procedures of use, methods and techniques for various application in engineering. In this sense, in order to enable its use in sustainable technological applications and, consequently, potentiate a natural and abundant resource in the Amazon, the present work aimed at the physical-mechanical characterization of the Inajá petiole. The petioles used in the mechanical tests were unfolded, sectioned and tested according to the American Standard Method ASTM D143-09. To obtain the density of the petioles, the mass and volume ratio of the specimens at 12% humidity was used. Inajá presented apparent density of 0.191 g / cm³. The correlations showed that regardless of the applied effort, the strength and stiffness properties will be directly related to its density.
Keywords: Inajá; Recurso natural; Amazônia; CNPQ::CIÊNCIAS EXATAS E DA TERRA